Outcomes for intra-substance free coracoid graft in patients with antero-inferior instability and glenoid bone loss in a population of high-risk athletes at a minimum follow-up of 2 years. Issue 1 (January 2015) - Arianjam, Afshin; Bell, Simon N; Coghlan, Jennifer; Old, Jason; Sloan, Roger
Background: The aim of this retrospective case series study was to assess the outcomes of patients with recurrent anterior shoulder instability with antero-inferior glenoid bone loss treated with a specific open stabilization technique using intra-substance coracoid bone-grafting and Bankart repair. Methods: Over a 4-year period, 34 shoulders in all male patients of mean age 21 years were stabilized with this technique. Pre- and postoperative function, motion and stability were assessed as part of Rowe stability scoring, and American Shoulder and Elbow Surgeons (ASES) and Oxford Instability were recorded, with at least 2 years of follow-up in all patients. Union of the graft was determined by post-operative computed tomography (CT) of the affected shoulder. Results: For all cases, two redislocations (5.9%) and two subluxations occurred when continuing high-risk sport after 2 years. Post-operative scores [median, mean (SD): Rowe 77.5, 77.2 (19.5); ASES 94.2, 92 (7.7); Oxford 43, 41.2 (6)]. CT scans on 28 shoulders at a mean of 4.5 months after surgery showed non-union in three cases (10%). Conclusions: These results demonstrate a high rate of success in cases of glenoid bone loss in the young contact athlete with recurrent instability treated with open stabilization and bone grafting.